Landscape evolution in the area of Kazimierski Landscape Park - Sobczyński Daniel; Karsznia Izabela (Polish Cartographical Review, 2019)
The presented research concerning the landscape evolution of the area of the Kazimierski Landscape Park assumed the analysis of landscape changes that took place in the western part of the Nałęczów Plateau in eastern Poland as a result of increased anthropopressure. To achieve this goal, the diverse data was employed: archives of the “Archeological Survey of Poland” obtained from the National Heritage Board of Poland, the registry data from the 16th century made available as part of the “Atlas Fontium” project elaborated by the Institute of History of the Polish Academy of Sciences, old map of the Western Galicia from 1808, a tactical map of the Military Geographical Institute in Warsaw from 1937, and the “Topographic Objects Database” (BDOT10k) obtained from the Head Office of Geodesy and Cartography. Based on the analysed data, maps presenting the development of the settlement network from the moment of permanent settlement of the area up to the present state and maps showing the changes in land use in the Kazimierski Landscape Park over the last centuries have been designed.